2020
DOI: 10.1186/s12889-020-08780-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to intergenerational communication in caregivers’ narratives regarding young people’s sexual and reproductive health and lifestyle in rural South Africa

Abstract: Background: Statistics from South Africa show the world's highest HIV prevalence with an estimated seven million people living with the virus. Several studies have pointed to communication about sexuality between parents/ caregivers and children as a protective factor. However, communication between generations has been described as problematic, especially due to discomfort in discussing sexual matters. The aim of this study was to explore how caregivers in a poor, rural part of South Africa talked about young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Linked to AGYW outcome expectancies described above, when AGYW view their parents’ attitudes as inflexible, outdated and irrelevant, and expect that engaging parents in SRH discussions will be fruitless or reactionary, AGYW avoid such interactions. Interventions for AGYW SRH in South Africa need to be sensitive towards socio-cultural norms, the traditional morals, and expectations of the older generation, while emphasising the importance of communication across generational boundaries (Nilsson, Edin, Kinsman, Kahn, & Norris, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linked to AGYW outcome expectancies described above, when AGYW view their parents’ attitudes as inflexible, outdated and irrelevant, and expect that engaging parents in SRH discussions will be fruitless or reactionary, AGYW avoid such interactions. Interventions for AGYW SRH in South Africa need to be sensitive towards socio-cultural norms, the traditional morals, and expectations of the older generation, while emphasising the importance of communication across generational boundaries (Nilsson, Edin, Kinsman, Kahn, & Norris, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to address barriers relating to parents’ self-efficacy, it would be beneficial for interventions to include strategies that provide parents/caregivers with a knowledge base and skill-set, to enhance their motivation and confidence in communicating around SRH topics with their adolescents, and create opportunities for communication and collaboration among parents/caregivers (AVAC, 2018 ; Guilamo-Ramos et al, 2008 ; Seif et al, 2018 ). The provision of knowledge to parents is one key ingredient, but must be combined with efforts to empower parent/caregivers, validating and addressing their potential discomfort towards talking about sex, and working to build their courage in discussing SRH, which will in turn increase their ability to be responsive to the needs of adolescents and support them to make safe and informed decisions about sex (Grossman et al, 2017 ; Nilsson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important consideration for program design is to create programs that target parent/caregiver-adolescent pairs as there is PLOS ONE some evidence that they are effective [49]. The interventions that mediate the intergenerational gaps between parents and adolescents by finding a common ground for them are likely to be effective interventions as such gaps have been implicated in poor parent-adolescent communications [50]. Some interventions may be presented via traditional and social media in order to bring them to scale.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cultural and religious structures, personal knowledge and discomfort also affect parent's ability to have these conversations (Vilanculos and Nduna 2017). Research with adults in a rural South African context has shown that adults perceive their children to be modern, and themselves to be traditional, making intergenerational communication about issues of sex and lifestyle difficult (Nilsson et al 2020). Other research focused on maternal HIV disclosure has found that mothers felt a lack of capacity to have conversations with their children about sex-related issues but knew it was necessary, while not being sure how to initiate and conduct these discussions (Mkwanazi, Rochat, and Bland 2017).…”
Section: Introductionmentioning
confidence: 99%